2001
DOI: 10.1096/fsb2fj000383com
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR3gene structure, regulatory region, and sequence polymorphisms

Abstract: Vascular endothelial growth factor receptor 3 (VEGFR‐3) is required for cardiovascular development during embryogenesis. In adults, this receptor is expressed in lymphatic endothelial cells, and mutant VEGFR3 alleles have been implicated in human hereditary lymphedema. To better understand the basis of its specific endothelial lineage‐restricted expression, we have characterized the VEGFR3 gene and its regulatory 5′ flanking region. The human gene contains 31 exons, of which exons 30a and 30b are alternatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
19
0
4
Order By: Relevance
“…Without functional data, the possibility remains that the identified change encodes a coding polymorphism. However, previous inquires by Iljin et al [2001] and Evans et al [2003] identified six and four polymorphisms, respectively, in the VEGFR3 coding region, none of which encoded the Q1020L missense mutation. Additionally, twelve other coding SNPs in the VEGFR3 gene (rs307821, rs307826, rs448012, rs744282, rs1049076, rs1049077, rs1049080, rs1130378, rs1130379, rs2270519, rs3736061, and rs3736062) are reported in the SNP database (NCBI) which also do not encode the Q1020L mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without functional data, the possibility remains that the identified change encodes a coding polymorphism. However, previous inquires by Iljin et al [2001] and Evans et al [2003] identified six and four polymorphisms, respectively, in the VEGFR3 coding region, none of which encoded the Q1020L missense mutation. Additionally, twelve other coding SNPs in the VEGFR3 gene (rs307821, rs307826, rs448012, rs744282, rs1049076, rs1049077, rs1049080, rs1130378, rs1130379, rs2270519, rs3736061, and rs3736062) are reported in the SNP database (NCBI) which also do not encode the Q1020L mutation.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR3 encodes a receptor tyrosine kinase that is expressed by lymphatic endothelial cells (LECs) [Kaipainen et al, 1995; Partanen et al, 2000] and is activated by the vascular endothelial growth factors VEGF‐C and VEGF‐D to mediate lymphangiogenesis [Veikkola et al, 2001]. The VEGFR3 gene is composed of 31 exons transcribed as two alternatively spliced transcripts encoding a protein with 7 immunoglobulin‐like repeat domains and 2 tyrosine kinase domains [Iljin et al, 2001]. Only 17 VEGFR3 mutations have been identified, and all mutations described localize to one of the two tyrosine kinase domains, illustrating the necessity of these domains in the signal transduction function of VEGFR3 [Ferrell et al, 1998; Irrthum et al, 2000; Karkkainen et al, 2000; Evans et al, 2003; Daniel‐Spiegel et al, 2005; Mizuno et al, 2005; Ghalamkarpour et al, 2006; Spiegel et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…; Iljin et al . ). Although flt4 is thought to play a role in the maintenance of the lymphatic endothelium and/or in lymphangiogenesis in adults, several recent observations have suggested that flt4 may play a role in lung angiogenesis during embryonic development (Kaipainen et al .…”
Section: Discussionmentioning
confidence: 97%
“…82,83,[86][87][88][89][90][91][92] The VEGFR-3 receptor, which is activated by VEGF-C and VEGF-D to mediate lymphangiogenesis, 93 is made up of an extracellular ligand-binding domain containing seven immunoglobulin homology regions, and two intracellular tyrosine kinase domains. 94 All VEGFR-3 mutations associated with Milroy's disease localize to one of these two tyrosine kinase domains, illustrating the necessity of these domains in the signal transduction function of VEGFR-3. 82 It is believed that the VEGFR-3 mutations in Milroy's disease result in defective VEGF-C and VEGF-D signaling due to dominant negative inhibition of VEGFR-3 autophosphorylation.…”
Section: Genetic Alterations In Human Lymphatic Diseasementioning
confidence: 99%